Formação acadêmica e prática docente: embates para o ensino de Estudos Amazônicos nas escolas municipais de Ananindeua-PA - COSTA, Ingrid Larêdo Leão da (2022)
This research aimed to analyze the way in which teachers, in elementary school classes, introduce the discipline of Amazonian Studies from public schools in the municipality of Ananindeua. Questionnaires carried out with professors assigned to the discipline are the main sources of this research, used to identify the professor’s profile, professional training and experience and relationship with the discipline. In addition, from the questionnaires, it is possible to score the workload allocated to the Amazonian Studies subject, the teaching materials used and the themes selected by the professors. The objective of the research is to understand how the variables, of formation, instruction and area in which it works, influence the teaching practice and the teaching-learning process of the students, since the discipline of Amazonian Studies is essential for the student to understand the importance of the region to which it is inserted.